English Speaking Activities In Kampung Inggris Pare: Unpacking The EFL Students’ Attitudes - Hilarius Raditya Priambada Purba; Muhammad Raihan; Theodesia Lady Pratiwi (UNIB Press, 2024)
This study aims to analyze student attitudes through affective components namely self-confidence, anxiety, feelings, and values in English speaking activities in English village. The influence through affective components can be seen through the experience of students, the participants in this study are class b2 students at the basic speaking level in Kampung Inggris 2023. This research applies qualitative methods, with questionnaires and interviews to collect data. The results showed that students have an influence on the affective component with different problems and experiences. The experience is divided into two, namely positive and negative, positive experiences have a positive impact on the development of students in English-speaking activities, while negative developments will hinder the development of students in Kampung Inggris. Students also have strategies, know how to solve problems internally and externally and understand how to develop themselves in English-speaking activities.